Principals' intellectual stimulation and teachers’ job satisfaction in public secondary schools - Olaolu Paul Akinnubi; Moses Adeleke Adeoye (Universitas Pendidikan Indonesia, 2024)
This study examined the relationship between principals' intellectual stimulation and teachers' job satisfaction in public secondary schools in Oyo State, Nigeria. This study identified specific intellectual stimulation strategies employed by principals to assess the level of job satisfaction among teachers and evaluate the effectiveness of these strategies. A descriptive research design was used for the study. A random sampling technique was used to select 352 teachers from 30 public secondary schools in nine local government areas in Oyo State, Nigeria. The findings indicate that teachers who perceived their principals as intellectually stimulating reported higher job satisfaction. The findings revealed that certain intellectual stimulation strategies positively impact teachers' job satisfaction, highlighting the importance of leadership practices in educational settings. It suggests that teachers who perceive their principals as intellectually stimulating are more likely to be satisfied with their jobs, motivated to perform at their best, and more committed to their professional roles. The study concludes that principals must embrace their role as intellectual stimulators and champions of continuous learning to cultivate a positive work environment. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara stimulasi intelektual kepala sekolah dan kepuasan kerja guru di Sekolah Menengah Negeri di Negara Bagian Oyo, Nigeria. Studi ini bertujuan untuk mengidentifikasi dan mengevaluasi efektivitas strategi stimulasi intelektual yang digunakan oleh kepala sekolah untuk menilai tingkat kepuasan kinerja guru. Desain penelitian yang digunakan pada studi ini adalah penelitian deskriptif. Teknik pengambilan data yang digunakan adalah teknik random sampling untuk memilih 352 guru dari 30 Sekolah Menengah Negeri di sembilan wilayah pemerintah daerah di Negara Bagian Oyo, Nigeria. Temuan menunjukkan bahwa kepala sekolah yang menerapkan strategi secara intelektual melaporkan kepuasan kerja yang lebih tinggi. Temuan mengungkapkan bahwa kepala sekolah yang melakukan stimulasi intelektual berdampak positif pada kepuasan kerja guru dan memperlihatkan pentingnya praktik kepemimpinan dalam lingkungan pendidikan. Hal ini memperlihatkan kepala sekolah yang dapat menstimulasi secara intelektual cenderung membuat guru lebih puas dengan pekerjaan mereka, termotivasi untuk bekerja sebaik mungkin, dan dapat lebih berkomitmen secara profesional. Studi ini menyimpulkan bahwa kepala sekolah harus menjalankan peran mereka sebagai stimulator intelektual dan pendukung pembelajaran berkelanjutan untuk menumbuhkan lingkungan kerja yang positif. Kata Kunci: kepemimpinan kepala sekolah; kepemimpinan transformasional; kepuasan kerja guru; stimulasi intelektual